Measure and estimation of the evapotranspiration of tomato plants cultivated with organic fertilization in protected ambient - Duarte, Georgea Rita Burck; Schöffel, Edgar Ricardo; Mendez, Marta Elena Gonzales; Paula, Viviane Aires de (Semina: Ciências Agrárias, 2010)
The present work had the aim of determining the water consumption for tomato crop cultivated in protected ambient under organic fertilization and of evaluating the estimates of evapotranspiration and of crop coefficients (Kc) in greenhouse, with the use of the methods Class A Pan, Solar Radiation, Penman and Penman-Monteith. The experiment was carried out from September/2004 to January/2005, at the Campus of Universidade Federal de Pelotas, Brazil. The organic fertilization of the soil consisted of two doses of vermicompost from bovine manure, and 'Floradade' tomato plants were transplanted in 4/11/2004, with 0.50 x 0.70 m spacing. In the central part of the greenhouse, a datalogger was installed in order to receive the signals originated from the agrometeorologicals sensors installed in the greenhouse. In order to determine the water consumption of the plants, the method of water balance of the soil was used associated to evapotranspirometers, constructed in the central of the polyethylene greenhouse. The water consumption of the tomato plants in the 88 days of cultivation was of 477 mm. The estimation of the evapotranspiration for the methods Class A Pan, Solar Radiation and Penman, presented high precision and had agreement with the measured values of the crop evapotranspiration. The reference evapotranspiration presented values close to the crop evapotranspiration during the crop growth with the use of the methods Class A Pan, Solar Radiation and Penman, with Kc values of 0.95; 1.02; and 1.01, respectively, while for the Penman-Monteith method the Kc was 1.41.